Bestimmung der thermischen Transporteigenschaften poröser Elektroden von Lithium-Ionen Batterien - Oehler, Dieter (KIT Scientific Publishing, 2021)
This contribution presents an analytical and a numerical model for predicting the effective thermal conductivity of porous electrode coatings as a function of microstructure parameters. Both models account for the morphological parameters and the thermal bulk materials of the constitutive cell components. The results of both models have been successfully verified against each other and validated with literature data as well as own experimental measurements.